Diagnóstico de los factores de riesgo de la carga física en los trabajadores(as) de las UDIV de la carrera Agrícola ESPAM-MFL - Ballén Faubla, Gema Liseth (2014)
I do this research is in the Escuela Superior Politécnica Agropecuaria de Manabí MFL teaching units, research and linking of the career of Agricola in the Bolívar, city of Calceta, over a period of nine months. In order to make a diagnosis of the risk factors of the physical load of the workers of the Agricola ESPAM-MFL career UDIV, research used investigative methods which helped to obtain information and at the same time were used, tools and techniques including interview, survey, map of the body that were an important part in the necessary compilation which gave way to the diagnostic process with bibliographic information, methods and tools for their subsequent election were characterized, these were of vital importance since served aid for the estimation of the risk factors of the physical burden of civil servants (as) field of the area of study units, we designed a procedure that consists of four stages: familiarization with the area of study Ergonomic assessment of physical load, processing and analysis of results and proposed a plan of improvement, each with their sub-stages. During the procedure, the results were obtained for later analysis presented in tables, figures and statistical charts and it is here where researchers with detailed study could make the decisions for the proposal of a better plan